Historical blocking: CN 2022-07-10 to 2022-07-16 (China) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2022-0340. Severity: critical. Confidence: 99%